Ternary precursors, methods of making and using the same
Patent Information
- Application Number
- CN202610899317.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]然而,更多的锂离子脱嵌会导致正极材料在充放电过程中发生更显著的晶格膨胀与收缩,容易引发结构坍塌、二次颗粒破碎、一次颗粒微裂纹、材料电阻率快速上升、循环性能急剧衰退等问题
[0006]本发明旨在至少在一定程度上解决相关技术中的技术问题之一。为此,本发明提供了一种三元前驱体及其制备方法与应用,该三元前驱体在X射线衍射(XRD)谱图中,(001)、(101)两个晶面衍射峰同时具有超窄半峰宽,且一次颗粒具有高长径比,为锂离子的扩散提供了更短的、径向的直线通道,能够显著改善正极材料的倍率性能。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, specifically to a ternary precursor, its preparation method, and its application. Background Technology
[0002] With the development of new energy technologies, the demand for high-energy-density lithium-ion batteries from electric vehicles and various energy storage systems is increasing. Ternary cathode materials, due to their advantages such as low cost, large discharge capacity, stable structure, good cycle performance, and thermal stability, have become the most widely used type of lithium-ion battery cathode material.
[0003] Nickel-cobalt-manganese hydroxide Ni x Co y Mn z (OH)₂(x+y+z=1), as a ternary precursor for ternary cathode materials, exhibits a certain degree of "hereditary" physicochemical properties in its morphology, structure, and elemental ratios, directly determining the electrochemical performance of the cathode material. Therefore, structural optimization of the ternary precursor is a key step in improving the performance of cathode materials.
[0004] In recent years, with the increasing demand for energy density, ternary precursors have gradually moved towards high nickel content. High-nickel ternary materials with nickel content ≥80 mol% (such as Ni8 series) have achieved large-scale mass production, while ultra-high nickel materials with nickel content ≥90 mol% have become a hot topic in industry research and development due to the reduction of cobalt content to below 10 mol%, which improves capacity while reducing cost.
[0005] However, more lithium-ion insertion and extraction can lead to more significant lattice expansion and contraction of the cathode material during charging and discharging, which can easily cause problems such as structural collapse, secondary particle breakage, primary particle microcracks, rapid increase in material resistivity, and sharp decline in cycle performance. Summary of the Invention
[0006] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention provides a ternary precursor, its preparation method, and its application. In the X-ray diffraction (XRD) spectrum, the (001) and (101) crystal plane diffraction peaks of this ternary precursor both have ultra-narrow half-widths, and the primary particles have a high aspect ratio, providing a shorter, radially linear channel for lithium-ion diffusion, which can significantly improve the rate performance of the cathode material.
[0007] A first aspect of the present invention provides a ternary precursor comprising secondary particles formed by the stacking of primary particles, wherein the average aspect ratio of the primary particles is 6 to 7; the ternary precursor satisfies: FWHM(001)≤0.4 and FWHM(101)≤0.41, wherein FWHM(001) represents the half-width at half-maximum (WHM) of the (001) crystal plane diffraction peak in the XRD pattern of the ternary precursor, and FWHM(101) represents the half-width at half-maximum (WHM) of the (101) crystal plane diffraction peak in the XRD pattern of the ternary precursor.
[0008] Therefore, the narrow half-width at half-maximum (WHM) of specific crystal planes in the ternary precursor, combined with the high aspect ratio of the whiskers, simultaneously optimizes lithium-ion transport dynamics from both the lattice interior and particle structure dimensions. Specifically, the narrow WHM of the diffraction peaks of the (001) and (101) crystal planes gives the ternary precursor high crystallinity and low microstrain, resulting in fewer lattice defects in the cathode material after sintering. Consequently, the lattice expansion and contraction of the cathode material are more uniform during charging and discharging. The whiskers with a high aspect ratio can form a continuous ion-conducting framework, enabling lithium ions to be transported rapidly along the long axis of the primary particles, improving the ion transport rate of the cathode material and thus reducing the internal resistance of the battery. The synergistic effect of these two factors significantly improves the lithium-ion diffusion coefficient, fundamentally solving the technical problem of poor rate performance of high-nickel materials.
[0009] According to an embodiment of the present invention, the ternary precursor may further include at least one of the following additional technical features: According to an embodiment of the present invention, the ternary precursor satisfies at least one of the following conditions: The average thickness of the primary particles is 90~130 nm; The average length of the primary particles is 600~900 nm; The primary particles are radially arranged and stacked to form secondary particles; The sphericity of the secondary particles is 0.8~1.0.
[0010] According to an embodiment of the present invention, the ternary precursor satisfies at least one of the following conditions: The specific surface area of the ternary precursor is 7~9 m². 2 / g; The porosity of the ternary precursor is 3-6%; The ternary precursor satisfies 1.0≤I(101) / I(001)≤1.2, where I(101) represents the intensity of the diffraction peak of the (101) crystal plane in the XRD pattern of the ternary precursor, and I(001) represents the intensity of the diffraction peak of the (001) crystal plane in the XRD pattern of the ternary precursor.
[0011] According to an embodiment of the present invention, the chemical formula of the ternary precursor satisfies: Ni x Co y Mn z (OH)2, where 0.9≤x<1.0, 0<y<0.1, 0<z<0.1, and x+y+z=1.
[0012] A second aspect of the present invention provides a method for preparing the aforementioned ternary precursor, comprising: A first coprecipitation reaction is carried out under a protective gas atmosphere with metal salt, precipitant, and complexing agent to obtain the first crystal nucleus; the metal salt includes nickel salt, cobalt salt, and manganese salt; the ammonia value in the first coprecipitation reaction system is controlled at 1~3 g / L, the pH is controlled at 11~12 in the early stage, and the pH is stabilized at 10±0.1 after 1.5h; The first crystal nucleus, metal salt, precipitant, and complexing agent are subjected to a second coprecipitation reaction under a protective gas atmosphere to obtain the second crystal nucleus; the ammonia value in the second coprecipitation reaction system is controlled at 6~8 g / L, and the pH is controlled at 9~11; the temperature of the second coprecipitation reaction is 60~80℃. The supernatant is continuously discharged to keep the liquid level in the reaction system constant; and an oxidizing gas is introduced to continue the reaction to obtain the ternary precursor; wherein the volume fraction of oxygen in the oxidizing gas is 2-8%.
[0013] According to embodiments of the present invention, the above method may further include at least one of the following additional technical features: According to an embodiment of the present invention, the method satisfies at least one of the following conditions: The molar ratio of nickel, cobalt, and manganese in the metal salt is x:y:z, where 0.9 ≤ x < 1.0, 0 < y < 0.1, 0 < z < 0.1, and x + y + z = 1; The nickel salt is at least one of nickel sulfate or nickel chloride; The cobalt salt is at least one of cobalt sulfate or cobalt chloride; The manganese salt is at least one of manganese sulfate or manganese chloride; The precipitant includes at least one of NaOH, KOH, Na2CO3, and NaHCO3; The complexing agent includes at least one of ammonia, ammonium carbonate, and ammonium bicarbonate. The solvent used in this method is water; The protective gas includes at least one of nitrogen, argon, and helium.
[0014] According to an embodiment of the present invention, the method satisfies at least one of the following conditions: The temperature of the first coprecipitation reaction is 40~60℃; The stirring speed for the first coprecipitation reaction is 300~500 rpm; The D50 of the first crystal nucleus is 3~6 μm.
[0015] According to an embodiment of the present invention, the method satisfies at least one of the following conditions: The stirring speed for the second coprecipitation reaction is 100~400 rpm; The D50 of the ternary precursor is 12~16 μm.
[0016] A third aspect of the present invention provides a cathode material prepared using the aforementioned ternary precursor and / or a ternary precursor obtained by the aforementioned method as raw materials. Thus, the cathode material possesses all the features and advantages of the aforementioned ternary precursor or preparation method, which will not be elaborated further here.
[0017] A fourth aspect of the present invention provides a lithium-ion battery comprising the aforementioned positive electrode material. Thus, the lithium-ion battery possesses all the features and advantages of the aforementioned positive electrode material, which will not be repeated here.
[0018] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0019] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 The image shows the SEM image of the ternary precursor obtained in Example 1 of this invention at a magnification of 10,000. Figure 2 The image shows the SEM image of the ternary precursor obtained in Example 1 of this invention at a magnification of 1000x. Figure 3 This is a SEM image of the ternary precursor obtained in Comparative Example 1 of the present invention at a magnification of 10,000. Figure 4 This is a SEM image of the ternary precursor obtained in Comparative Example 1 of the present invention at a magnification of 1000x. Figure 5 The image shows the XRD pattern of the ternary precursor obtained in Example 1 of this invention. Detailed Implementation
[0020] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0021] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this invention, unless otherwise stated, "a plurality of" means two or more.
[0022] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0023] In this document, the terms “comprising” or “including” are open-ended expressions, meaning that they include the contents specified in this invention, but do not exclude other aspects.
[0024] In this document, the terms “optionally,” “optionally,” or “optionally” generally refer to an event or condition that may, but may not, occur, and the description includes both cases in which the event or condition occurs and cases in which the event or condition does not occur.
[0025] By controlling the crystal structure and primary particle morphology, problems such as structural collapse, secondary particle breakage, primary particle microcracks, rapid increase in material resistivity, and sharp decline in cycle performance that easily occur in cathode materials during charging and discharging can be improved.
[0026] Exposing more (001) and (101) active crystal planes can effectively reduce the internal resistance of the material and improve its output characteristics. This is because Li + Diffusion resistance is closely related to the diffusion path length and transport channel area: the shorter the diffusion path and the larger the transport channel area, the lower the diffusion resistance; the abundant pores inside the material allow for sufficient electrolyte wetting, further shortening the diffusion path. + The diffusion path is optimized. Furthermore, the high aspect ratio primary particles with uniform size and morphology can shrink and densify more evenly during sintering, forming structurally complete secondary spherical particles with low internal stress. These particles have high strength and are not easily broken during electrode slurry stirring, coating, and rolling. The slender primary particles also provide shorter and more consistent radial straight channels for lithium ion diffusion, allowing lithium ions to quickly embed and extract along the sidewalls of the primary particles without having to cross many grain boundaries, thus significantly reducing ion transport resistance and resulting in a significant improvement in capacity retention at high rates.
[0027] However, ternary precursors prepared by related technologies generally suffer from the following problems: (1) Insufficient crystallinity of crystals. Specifically, the active crystal planes such as (001) and (101) have poor crystallinity and low XRD diffraction peaks. During co-precipitation, the crystals tend to grow along the a-axis and b-axis, resulting in excessively large closed crystal plane size and longer lithium-ion transport paths, which is not conducive to high-rate performance. (2) Poor control of primary particle morphology. Specifically, traditional processes make it difficult to achieve precise control of primary particle morphology. Usually, the resulting particles are uneven in morphology and have a small aspect ratio, which leads to inconsistent shrinkage and internal stress concentration during sintering, and prolonged lithium ion diffusion, ultimately affecting the battery's energy density, first charge and discharge efficiency and cycle stability.
[0028] To address the aforementioned technical problems, this invention provides a novel ternary precursor, which aims to improve lithium-ion diffusion efficiency, energy density, first charge-discharge efficiency, and cycle stability by optimizing the crystal structure and primary particle morphology, thereby achieving ultra-narrow half-width and high crystallinity of the (001) and (101) crystal planes, as well as high aspect ratio and radial arrangement of the primary particles.
[0029] In view of this, a first aspect of the present invention provides a ternary precursor comprising secondary particles formed by the stacking of primary particles, wherein the average aspect ratio of the primary particles is 6 to 7; the ternary precursor satisfies: FWHM(001)≤0.4 and FWHM(101)≤0.41, wherein FWHM(001) represents the half-width at half-maximum (WHM) of the (001) crystal plane diffraction peak in the XRD pattern of the ternary precursor, and FWHM(101) represents the half-width at half-maximum (WHM) of the (101) crystal plane diffraction peak in the XRD pattern of the ternary precursor.
[0030] Therefore, the narrow half-width at half-maximum (HWHM) of specific crystal planes in the ternary precursor, combined with the high aspect ratio of the whiskers, simultaneously optimizes lithium-ion transport dynamics from both the lattice interior and particle structure dimensions. Specifically, the narrow HWHM of the diffraction peaks on the (001) and (101) crystal planes gives the ternary precursor high crystallinity and low microstrain, resulting in fewer lattice defects in the cathode material after sintering. Consequently, the lattice expansion and contraction of the cathode material are more uniform during charging and discharging. The whiskers with a high aspect ratio can form a continuous ion-conducting framework, enabling lithium ions to be transported rapidly along the long axis of the primary particles, improving the ion transport rate of the cathode material and thus reducing the internal resistance of the battery. The synergistic effect of these two factors significantly improves the lithium-ion diffusion coefficient, fundamentally solving the technical problem of poor rate performance of high-nickel materials.
[0031] In some embodiments, the average thickness of the primary particles is 90-130 nm. For example, the average thickness of the primary particles can be 90 nm, 95 nm, 100 nm, 105 nm, 110 nm, 115 nm, 120 nm, 125 nm, 130 nm, or any value range between two of these.
[0032] Therefore, an average particle thickness within the aforementioned range is beneficial for ensuring the radial growth orientation of the whiskers while providing sufficient lateral diffusion channels for lithium ions, achieving a good balance between improving rate performance and maintaining structural integrity. This avoids both the elongation of ion diffusion paths caused by excessively thick particles and the structural fragility caused by excessively thin particles.
[0033] In some embodiments, the average length of the primary particles is 600-900 nm. For example, the average length of the primary particles can be 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, etc.
[0034] Therefore, an average particle length within the aforementioned range is beneficial for constructing radially linear channels from the particle surface to the center. If the length is too short, it may weaken the contribution of radial alignment to shortening the diffusion path; if the length is too long, it may increase the risk of primary particles breaking during sintering or cycling.
[0035] In some embodiments, the primary particles are radially arranged and stacked to form secondary particles.
[0036] Therefore, the radially arranged stacking method helps to provide a low-torsion diffusion channel for lithium ions, enabling ions to quickly insert or extract along the whisker sidewalls, thereby reducing transport resistance and improving capacity performance at high rates; it can also better buffer volume changes, avoid stress concentration, and has high particle strength, which is beneficial to improving the rate capacity retention of cathode materials.
[0037] In some embodiments, the sphericity of the secondary particles is 0.8 to 1.0, specifically 0.80, 0.85, 0.90, 0.95, 0.98, etc.
[0038] Higher sphericity of secondary particles is beneficial for improving the flowability and dispersibility of ternary precursors and cathode materials, thereby obtaining more uniform electrode quality during electrode coating. If the sphericity is too low, it may lead to uneven particle packing density, which in turn affects the energy density and consistency of the battery.
[0039] In this invention, the sphericity is measured based on SEM images, and the calculation formula is: sphericity = 4πA / P², where A is the projected area of the particle, P is the projected perimeter of the particle, and the average value is taken after randomly counting no less than 50 secondary particles.
[0040] In some embodiments, the specific surface area of the ternary precursor is 7-9 m². 2 / g. For example, the specific surface area of the ternary precursor can be 7.0 m² / g, 7.5 m² / g, 8.0 m² / g, 8.5 m² / g, 9.0 m² / g, etc.
[0041] The aforementioned specific surface area range is beneficial for maintaining appropriate structural compactness while ensuring sufficient contact with the electrolyte. If the specific surface area is too high, it may exacerbate interfacial side reactions; if the specific surface area is too low, it may lead to insufficient lithium-ion diffusion channels, which is detrimental to improving rate performance.
[0042] In this invention, the specific surface area is determined by the BET method (i.e., the Brunauer-Emmett-Teller method), specifically referring to the standard GB / T 19587-2017 "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method".
[0043] In some embodiments, the porosity of the ternary precursor is 3-6%. For example, the porosity of the ternary precursor can be 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, etc.
[0044] Controlling the porosity within the aforementioned range helps maintain structural integrity during sintering and provides buffer space for volume expansion. Excessive porosity may reduce the mechanical strength of the particles; conversely, insufficient porosity may limit the wetting effect of the electrolyte.
[0045] In this invention, the porosity test method is as follows: after the secondary particles are cut by ion beam, their cross-section is directly observed by scanning electron microscope (SEM), and the area of the cut hole and the area of the whole cross-section are calculated by image analysis software (such as ImageJ), and the porosity is calculated according to the formula "porosity = area of cut hole / area of whole cross-section × 100%".
[0046] In some embodiments, the ternary precursor satisfies 1.0 ≤ I(101) / I(001) ≤ 1.2, where I(101) represents the intensity of the diffraction peak of the (101) crystal plane in the XRD pattern of the ternary precursor, and I(001) represents the intensity of the diffraction peak of the (001) crystal plane in the XRD pattern of the ternary precursor. For example, the peak intensity ratio I(101) / I(001) of the ternary precursor can be 1.0, 1.05, 1.1, 1.15, 1.2, etc.
[0047] The range of the I(101) / I(001) ratio reflects the growth competition relationship of the crystal along different crystal planes. A suitable peak intensity ratio helps to expose more active crystal planes that are conducive to lithium-ion transport. If the I(101) / I(001) ratio is too high, it may mean that a certain crystal plane is overgrown, which will disrupt the anisotropic balance of the structure; if the I(101) / I(001) ratio is too low, it may lead to the obstruction of ion transport channels, which is not conducive to improving the output characteristics of the cathode material.
[0048] It should be noted that in this invention, FWHM(001), FWHM(101) and I(101) / I(001) are measured by powder X-ray diffraction (XRD); the XRD test uses Cu Kα radiation, tube voltage 40kV, tube current 40mA, scanning range 5°~10°, step size 0.02°, scanning rate 2° / min; FWHM is the half-width at half maximum (WHM) of the corresponding diffraction peak after background subtraction, and I(101) and I(001) are the peak height intensities after background subtraction.
[0049] According to an embodiment of the present invention, the chemical formula of the ternary precursor satisfies: Ni x Co y Mn z (OH)2, where 0.9≤x<1.0, 0<y<0.1, 0<z<0.1, and x+y+z=1.
[0050] For example, the molar content x of nickel can be 0.90, 0.92, 0.94, 0.96, 0.98, etc.; the molar content y of cobalt can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, etc.; and the molar content z of manganese can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, etc.
[0051] Therefore, controlling the nickel content to above 90% is beneficial for significantly improving the discharge specific capacity of cathode materials prepared from ternary precursors, thereby meeting the requirements for high energy density. Simultaneously, controlling the cobalt content to a lower level helps reduce material costs and lessen dependence on cobalt resources; similarly controlling the manganese content to this lower level can maintain the stability of the layered structure to a certain extent. If the cobalt or manganese content is too high, it may actually sacrifice some of the capacity advantage.
[0052] A second aspect of the present invention provides a method for preparing the aforementioned ternary precursor, comprising: A first coprecipitation reaction is carried out under a protective gas atmosphere with metal salt, precipitant, and complexing agent to obtain a first crystal nucleus; the metal salt includes nickel salt, cobalt salt, and manganese salt; the ammonia value in the first coprecipitation reaction system is controlled at 1~3 g / L, and the pH is controlled at 11~12; The first crystal nucleus, metal salt, precipitant, and complexing agent are subjected to a second coprecipitation reaction under a protective gas atmosphere to obtain a second crystal nucleus; the ammonia value in the second coprecipitation reaction system is controlled at 6~8 g / L, the pH is controlled at 9~11 in the early stage, and the pH is stabilized at 10±0.1 after 1.5h; the temperature of the second coprecipitation reaction is 60~80℃. The supernatant is continuously discharged to keep the liquid level in the reaction system constant; and an oxidizing gas is introduced to continue the reaction to obtain the ternary precursor; wherein the volume fraction of oxygen in the oxidizing gas is 2-8%.
[0053] Therefore, by controlling the preparation process, the crystal structure, primary particle morphology, and orientation of the ternary precursor can be significantly improved. Specifically, a first coprecipitation reaction is carried out under low ammonia value and high pH conditions to obtain the first crystal nucleus, followed by a second coprecipitation reaction under high ammonia value and low pH conditions. Through a synergistic control strategy of ammonia value and pH, it is beneficial to guide the cell growth along a specific direction, thereby obtaining a ternary precursor structure with good crystallinity and ultra-narrow half-maximum width at half-maximum (HWHM).
[0054] Controlling the temperature of the second coprecipitation reaction within the aforementioned range is beneficial for providing sufficient thermodynamic driving force for the growth of unit cells along a specific direction, promoting the radially preferential growth of primary particles. If the temperature is too high, it may accelerate excessive grain growth, resulting in overly coarse primary particles, which is not conducive to the formation of slender whisker morphologies; if the temperature is too low, it may weaken the selectivity of crystal orientation growth, resulting in poor radial alignment, which in turn affects the degree of narrowing of the full width at half maximum (FWHM).
[0055] Furthermore, by adjusting the volume fraction of oxygen in the oxidizing gas, the oxygen injection rate can be precisely controlled, which is beneficial for improving the aspect ratio of the whiskers and forming a radially (radial) shaped, slender whisker morphology. If the volume fraction of oxygen is too low, the aspect ratio may be too low; if the volume fraction of oxygen is too high, the particle surface may be over-oxidized, affecting structural uniformity. This slender and highly uniform whisker structure helps to provide radial linear diffusion channels for lithium ions, allowing ions to quickly insert or extract along the particle sidewalls, thereby reducing transport resistance caused by crossing grain boundaries. At the same time, rod-shaped particles tend to oriented during electrode rolling, which is beneficial for achieving denser packing and reducing porosity, thereby increasing the coating amount per unit area and the electrode energy density.
[0056] For example, the ammonia value in the first coprecipitation reaction system can be 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L, 3 g / L, etc., and the pH can be 11.0, 11.2, 11.5, 11.8, 12.0, etc.; the ammonia value in the second coprecipitation reaction system can be 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, etc., and the pH can be 9.0, 9.5, 10.0, 10.5, 11.0, etc.; the temperature of the second coprecipitation reaction can be 60 ℃, 65 ℃, 70 ℃, 75 ℃, 80 ℃, etc.; and the volume fraction of oxygen in the oxidizing gas can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, etc.
[0057] In some embodiments, the molar ratio of nickel, cobalt, and manganese in the metal salt is x:y:z, where 0.9 ≤ x < 1.0, 0 < y < 0.1, 0 < z < 0.1, and x + y + z = 1. For example, the molar content x of nickel in the metal salt can be 0.90, 0.92, 0.94, 0.96, 0.98, etc.; the molar content y of cobalt can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, etc.; and the molar content z of manganese can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, etc.
[0058] Therefore, controlling the nickel content to above 90% is beneficial for obtaining a higher discharge specific capacity; while controlling the cobalt and manganese content to below 5% helps to maintain structural stability while reducing costs.
[0059] In some embodiments, the nickel salt is at least one of nickel sulfate or nickel chloride.
[0060] In some embodiments, the cobalt salt is at least one of cobalt sulfate or cobalt chloride.
[0061] In some embodiments, the manganese salt is at least one of manganese sulfate or manganese chloride.
[0062] Therefore, selecting metal salts from sulfate or chloride systems is beneficial for obtaining a stable metal ion release rate in the coprecipitation reaction, thereby improving the uniformity of the ternary precursor particles.
[0063] In some embodiments, the precipitant includes at least one selected from NaOH, KOH, Na₂CO₃, and NaHCO₃. This helps maintain the pH stability of the reaction system; however, if the precipitant is not chosen appropriately, it may lead to local fluctuations in supersaturation, thereby affecting the uniformity of particle morphology.
[0064] In some embodiments, the complexing agent includes at least one of ammonia, ammonium carbonate, and ammonium bicarbonate.
[0065] In some embodiments, the solvent of the method is water.
[0066] In some embodiments, the protective gas includes at least one of nitrogen, argon, and helium. This helps prevent the oxidation of metal ions, thereby ensuring the chemical compositional stability of the ternary precursor.
[0067] In some embodiments, the temperature of the first coprecipitation reaction is 40~60°C. For example, the temperature of the first coprecipitation reaction can be 40°C, 45°C, 50°C, 55°C, 60°C, etc.
[0068] Therefore, controlling the temperature of the first coprecipitation reaction within the above range is beneficial for obtaining initial crystal nuclei with uniform size. If the temperature is too high, it may accelerate the collision and aggregation of crystal nuclei, resulting in a wider particle size distribution. If the temperature is too low, it may reduce the reaction rate and affect production efficiency.
[0069] In some embodiments, the stirring speed of the first coprecipitation reaction is 300-500 rpm. For example, the stirring speed of the first coprecipitation reaction can be 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, etc.
[0070] This helps to maintain a uniform distribution of materials within the reaction system and prevent excessive local growth of particles. If the rotation speed is too high, excessive shear force may cause crystal nuclei to break. If the rotation speed is too low, it may cause particle sedimentation or agglomeration, affecting the consistency of the product.
[0071] In some embodiments, the D50 of the first crystal nucleus is 3~6 μm. For example, the D50 of the first crystal nucleus can be 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, etc.
[0072] Therefore, controlling the particle size of the first crystal nucleus within the above range is beneficial for providing seed particles with a concentrated particle size distribution for subsequent growth stages. If the particle size of the first crystal nucleus is too small, it may prolong the overall reaction time. If the particle size is too large, it may cause the particle size of the final product to exceed the target range, affecting batch stability.
[0073] It should be noted that, in this invention, D50 refers to the particle size corresponding to a cumulative particle size distribution percentage of 50% for powder materials, i.e., the median diameter or median particle size. Unless otherwise specified, the D50 in this invention is measured using a Malvern laser particle size analyzer.
[0074] In some embodiments, the stirring speed of the second coprecipitation reaction is 100~400 rpm. For example, the stirring speed of the second coprecipitation reaction can be 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, etc.
[0075] This helps to maintain good particle dispersion while providing a suitable collision environment for radial growth. If the rotation speed is too high, excessive shear force may disrupt the radial growth trend of the whiskers; if the rotation speed is too low, it may lead to particle agglomeration or uneven growth, affecting the consistency of the product.
[0076] In some embodiments, the D50 of the ternary precursor is 12-16 μm. For example, the D50 of the ternary precursor can be 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, etc.
[0077] Therefore, controlling the particle size of the ternary precursor within the aforementioned range is beneficial for balancing the processing performance of subsequent sintering processes with the energy density of the cathode material. If the particle size is too small, it may reduce the compaction density during electrode coating; if the particle size is too large, it may prolong the lithium-ion diffusion distance, which is not conducive to improving rate performance.
[0078] In some embodiments, the preparation method further includes post-treatment after the oxidizing gas is introduced and the reaction continues. The post-treatment includes washing, dehydration, sieving, iron removal, and packaging.
[0079] A third aspect of the present invention provides a cathode material prepared using the aforementioned ternary precursor and / or a ternary precursor obtained by the aforementioned method as raw materials. Thus, the cathode material possesses all the features and advantages of the aforementioned ternary precursor or preparation method, which will not be elaborated further here.
[0080] In some embodiments, the method for preparing the cathode material includes: mixing and calcining the ternary precursor with a lithium source to obtain the cathode material.
[0081] In some embodiments, the method for preparing the cathode material includes: mixing and calcining the ternary precursor with a lithium source and a doped metal source to obtain the cathode material.
[0082] It should be noted that the present invention does not particularly limit the specific type of doping element, and conventional modifying elements for cathode materials can be used for doping. For example, the doping element includes at least one of magnesium (Mg), sodium (Na), aluminum (Al), titanium (Ti), zirconium (Zr), yttrium (Y), zinc (Zn), chromium (Cr), barium (Ba), antimony (Sb), bismuth (Bi), tin (Sn), lanthanum (La), cerium (Ce), fluorine (F), Mg-F, Al-F, Ti-F, Mg-Al-F, and Mg-Ti-F.
[0083] A fourth aspect of the present invention provides a lithium-ion battery comprising the aforementioned positive electrode material. Thus, the lithium-ion battery possesses all the features and advantages of the aforementioned positive electrode material, which will not be repeated here.
[0084] The present invention will be explained below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0085] Example 1 A method for preparing the aforementioned ternary precursor includes: Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed to prepare a metal salt solution with a total concentration of 134 g / L and a nickel-cobalt-manganese molar ratio of 90:5:5. 100 L of pure water, 0.36 L of 320 g / L NaOH solution, and 2.3 L of 90 g / L ammonia solution were added to the reactor to obtain the first base solution; the pH of the first base solution was 11.75, and the ammonia concentration was 2 g / L; 0.5 m³ of ammonia solution was bubbled into the first base solution. 3 / h of N2, heated to 50℃ and kept stable; A metal salt solution, NaOH solution, and ammonia water were introduced into a first reactor containing a first base liquid to carry out a first coprecipitation reaction. By adjusting the amounts of NaOH solution and ammonia water, the ammonia concentration in the first coprecipitation reaction was consistently controlled at 2 g / L. The pH value was controlled at 11.75 in the early stage of the reaction. When the reaction time reached 1.5 h, the pH value was controlled at 10.0, and the rotation speed was maintained at 430 rpm. Through step-up flow, the flow rate of the metal salt solution was continuously increased from 4.2 L / h to 48 L / h over 16 h. When the particle D50 reached 5.0 μm, the feeding was stopped, and the first crystal nucleus was obtained. Add 150 L of pure water and 10 L of ammonia solution with a concentration of 90 g / L to the second reactor to obtain the second base solution; adjust the ammonia concentration of the second base solution to 6.5 g / L, and introduce 0.5 m... 3 The nitrogen (N2) was heated to 70°C and kept stable. The first crystal nucleus was added to the second reactor, and the metal salt solution, NaOH solution, and ammonia were simultaneously introduced into the second reactor to carry out the second coprecipitation reaction, obtaining the second crystal nucleus. By adjusting the amount of NaOH solution and ammonia, the ammonia concentration in the second coprecipitation reaction was always controlled at 6.5±0.5 g / L, and the pH value was always controlled at 10.0±0.1. The rotation speed was gradually reduced from 370 rpm to 140 rpm over 20 hours. The flow rate of the metal salt solution was controlled from 8 L / h and stabilized at 30 L / h after 20 hours. When particle D50 > 10 μm, the supernatant is continuously discharged to maintain a constant liquid level in the reaction system; an oxidizing gas with an oxygen volume fraction of 6% is introduced, and feeding is stopped when particle D50 reaches 14.5 μm; solid-liquid separation is performed, the separated filter cake is washed with sodium hydroxide solution, then rinsed with pure water, dried, sieved, and demagnetized to obtain the ternary precursor Ni. 0.9 Co 0.05 Mn 0.05 (OH)2.
[0086] Example 2 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the temperature of the second coprecipitation reaction in this embodiment is 60°C.
[0087] Example 3 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the temperature of the second coprecipitation reaction in this embodiment is 65°C.
[0088] Example 4 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the temperature of the second coprecipitation reaction in this embodiment is 75°C.
[0089] Example 5 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the volume fraction of oxygen in the oxidizing gas described in this embodiment is 2%.
[0090] Example 6 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the volume fraction of oxygen in the oxidizing gas described in this embodiment is 4%.
[0091] Example 7 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the volume fraction of oxygen in the oxidizing gas described in this embodiment is 8%.
[0092] Comparative Example 1 This comparative example is based on Example 1, and the only difference from Example 1 is that the temperature of the second coprecipitation reaction in this comparative example is 85°C, and the volume fraction of oxygen in the oxidizing gas is 10%.
[0093] Comparative Example 2 This comparative example is based on Example 1, and the only difference from Example 1 is that the temperature of the second coprecipitation reaction in this comparative example is 55°C, and the volume fraction of oxygen in the oxidizing gas is 1%.
[0094] Performance testing 1. SEM testing The ternary precursors prepared in Example 1 and Comparative Example 1 were subjected to SEM testing. Based on the SEM images, at least 50 primary particles were randomly tested using ImageJ software, and the average value was taken to obtain the average length, average thickness, and average aspect ratio of the primary particles. The results are as follows. Figures 1-4 As shown in Table 1.
[0095] 2. XRD test The ternary precursor prepared in Example 1 was subjected to XRD testing to obtain the values of FWHM(001) and FWHM(101), and the results are as follows. Figure 5 As shown in Table 1.
[0096] Table 1. Detection results of physicochemical properties of Examples 1-7 and Comparative Examples 1-2
[0097] Depend on Figures 1-4 It can be seen that the secondary particles in the ternary precursor prepared in Example 1 did not crack and there were basically no small particles generated, and the whisker uniformity was good; while the ternary precursor prepared in Comparative Example 1 showed nucleation phenomenon and the whisker uniformity was poor.
[0098] Depend on Figure 5As shown in Table 1, the ternary precursors prepared in Examples 1-7 of this invention have ultra-narrow half-widths of 001 and 101 peaks, good crystallinity, and an aspect ratio of 6-7 for the primary particles. The combination of these two factors can provide a shorter and more consistent lithium-ion diffusion path and electron conduction path, enabling the battery to maintain a high capacity even at high rates (fast charging), and giving the obtained cathode material excellent rate performance.
[0099] Compared with Example 1, Examples 2-4 show that as the temperature of the second coprecipitation reaction increases, the half-widths of 001 and 101 gradually narrow, and the minimum I(101) / I(001) is obtained at around 70℃ (Example 1). When the temperature of the second coprecipitation reaction reaches 75℃, I(101) / I(001) basically no longer decreases, and the synthesis temperature is high and the energy consumption is high. Therefore, the optimal synthesis temperature is 70℃.
[0100] Compared with Example 1, Examples 5-7 show that as the volume fraction of oxygen increases, the aspect ratio of the primary particles gradually increases. However, when the volume fraction of oxygen reaches 8%, the radial growth effect of the primary particles weakens and the aspect ratio decreases. Therefore, the optimal volume fraction of oxygen is 6%.
[0101] Comparing Example 1 and Comparative Example 1, it can be found that increasing the temperature of the second coprecipitation reaction and increasing the volume fraction of oxygen will lead to nucleation and a decrease in aspect ratio. Comparing Example 1 and Comparative Example 2, it can be found that decreasing the temperature of the second coprecipitation reaction and decreasing the volume fraction of oxygen will not only decrease the aspect ratio, but also increase the I(101) / I(001) of the XRD pattern and decrease the crystallinity.
[0102] 3. Electrical performance testing The ternary precursors obtained in Examples 1-7 and Comparative Examples 1-2 were sintered to prepare the corresponding ternary cathode materials, which were then assembled into lithium-ion batteries. The batteries were tested under 2.8-4.5V conditions at 2.0C / 2.0C (high rate) and 0.1C / 0.1C (low rate) charge-discharge regimes (four parallel tests were conducted, and the average value was taken). The charge specific capacity, discharge specific capacity, and initial charge-discharge efficiency were calculated. After the initial charge-discharge test, cycle tests were continued (four parallel tests were conducted, and the average value was taken). After 50 cycles, the capacity retention rate was calculated, and the results are shown in Tables 2-3.
[0103] The formula for calculating the specific capacity during the first charge is as follows: Specific charging capacity = Charging capacity / Mass of positive electrode material The formula for calculating the discharge specific capacity is: Discharge specific capacity = Discharge capacity / Mass of cathode material The formula for calculating the initial charge-discharge efficiency is as follows: First charge / discharge efficiency = (First discharge specific capacity / First charge specific capacity) × 100% The formula for calculating the capacity retention rate is: Capacity retention rate = (Specific capacity at 50th discharge cycle / Specific capacity at first discharge cycle) × 100% Table 2. Electrical performance test results of cathode materials under 2.0C / 2.0C charge / discharge regime.
[0104] Table 3. Electrical performance test results of cathode materials under 0.1C / 0.1C charge / discharge regime.
[0105] As shown in Tables 2 and 3, under the conditions of 2.8-4.5V and tested at a current density of 2.0C / 2.0C (high rate), Example 1 exhibits the highest initial charge-discharge efficiency and the best cycle stability, with a capacity retention rate of over 94% after 50 cycles. Under the conditions of 2.8-4.5V and tested at a current density of 0.1C / 0.1C (low rate), Example 1 exhibits the highest initial discharge specific capacity, approaching 230 mAh / g, and also shows the best cycle stability, with a capacity retention rate of over 98% after 50 cycles.
[0106] In the description of this specification, the references to terms such as "an embodiment," "some embodiments," "a method of implementation," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0107] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A ternary precursor, characterized in that, The ternary precursor includes secondary particles formed by the stacking of primary particles, wherein the average aspect ratio of the primary particles is 6 to 7; the ternary precursor satisfies: FWHM(001)≤0.4 and FWHM(101)≤0.41, wherein FWHM(001) represents the half-width at half-maximum (WHM) of the (001) crystal plane diffraction peak in the XRD pattern of the ternary precursor, and FWHM(101) represents the half-width at half-maximum (WHM) of the (101) crystal plane diffraction peak in the XRD pattern of the ternary precursor.
2. The ternary precursor according to claim 1, characterized in that, At least one of the following conditions must be met: The average thickness of the primary particles is 90~130 nm; The average length of the primary particles is 600~900 nm; The primary particles are radially arranged and stacked to form secondary particles; The sphericity of the secondary particles is 0.8~1.
0.
3. The ternary precursor according to claim 1, characterized in that, At least one of the following conditions must be met: The specific surface area of the ternary precursor is 7~9 m². 2 / g; The porosity of the ternary precursor is 3-6%; The ternary precursor satisfies 1.0≤I(101) / I(001)≤1.2, where I(101) represents the intensity of the diffraction peak of the (101) crystal plane in the XRD pattern of the ternary precursor, and I(001) represents the intensity of the diffraction peak of the (001) crystal plane in the XRD pattern of the ternary precursor.
4. The ternary precursor according to any one of claims 1 to 3, characterized in that, The chemical formula of the ternary precursor satisfies: Ni x Co y Mn z (OH)2, where 0.9≤x<1.0, 0<y<0.1, 0<z<0.1, and x+y+z=1.
5. A method for preparing the ternary precursor as described in any one of claims 1 to 4, characterized in that, include: A first coprecipitation reaction is carried out under a protective gas atmosphere with metal salt, precipitant, and complexing agent to obtain the first crystal nucleus; the metal salt includes nickel salt, cobalt salt, and manganese salt; the ammonia value in the first coprecipitation reaction system is controlled at 1~3 g / L, the pH is controlled at 11~12 in the early stage, and the pH is stabilized at 10±0.1 after 1.5h; The first crystal nucleus, metal salt, precipitant, and complexing agent are subjected to a second coprecipitation reaction under a protective gas atmosphere to obtain the second crystal nucleus; the ammonia value in the second coprecipitation reaction system is controlled at 6~8 g / L, and the pH is controlled at 9~11; the temperature of the second coprecipitation reaction is 60~80℃. The supernatant is continuously discharged to keep the liquid level in the reaction system constant; and an oxidizing gas is introduced to continue the reaction to obtain the ternary precursor; wherein the volume fraction of oxygen in the oxidizing gas is 2-8%.
6. The method according to claim 5, characterized in that, At least one of the following conditions must be met: The molar ratio of nickel, cobalt, and manganese in the metal salt is x:y:z, where 0.9 ≤ x < 1.0, 0 < y < 0.1, 0 < z < 0.1, and x + y + z = 1; The nickel salt is at least one of nickel sulfate or nickel chloride; The cobalt salt is at least one of cobalt sulfate or cobalt chloride; The manganese salt is at least one of manganese sulfate or manganese chloride; The precipitant includes at least one of NaOH, KOH, Na2CO3, and NaHCO3; The complexing agent includes at least one of ammonia, ammonium carbonate, and ammonium bicarbonate. The solvent used in this method is water; The protective gas includes at least one of nitrogen, argon, and helium.
7. The method according to claim 5 or 6, characterized in that, At least one of the following conditions must be met: The temperature of the first coprecipitation reaction is 40~60℃; The stirring speed for the first coprecipitation reaction is 300~500 rpm; The D50 of the first crystal nucleus is 3~6 μm.
8. The method according to claim 5 or 6, characterized in that, At least one of the following conditions must be met: The stirring speed for the second coprecipitation reaction is 100~400 rpm; The D50 of the ternary precursor is 12~16 μm.
9. A positive electrode material, characterized in that, The ternary precursor described in any one of claims 1 to 4 and / or the ternary precursor obtained by the method described in any one of claims 5 to 8 are used as raw materials to prepare the product.
10. A lithium-ion battery, characterized in that, Includes the cathode material as described in claim 9.